Monetary Policy Shocks to Commodity Prices: Evidence from Pakistan - Farhan Ahmed; Mushtaq Memon; Raza Ali (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
Monetary policy is always a dynamic attribute on commodity prices in the economy. This article examines the empirical relationship between monetary policy and commodity price by employing a vector auto-regression (VAR) Model to show its response in the case of Pakistan. In this paper, the research philosophy is employed based on Positivism with Deductive approach to recognizing the response of monetary policy shocks on commodity price. Recently, low-interest rates and excessive liquidity play a dynamic role in affecting the prices of the commodities market. Furthermore, the impact of monetary policy rate show significant result and seems to be huge in the economy of Pakistan massively. Besides, there is a stable relationship between monetary policy instrument and commodity prices even though the current financial crisis.